PENGARUH SELF-EFFICACY TERHADAP HASIL BELAJAR SISWA SEKOLAH DASAR NEGERI SE-KOTA KUPANG - Silvester P Taneo; Maxsel Koro (Jurnal Ilmu Pendidikan Jasmani Kesehatan Dan Olahraga, 2022)
Self-efficacy is one of the factors that contribute to the achievement of student learning outcomes, where through high self-efficacy students will have a high level of selfconfidence so that they can motivate students to achieve the expected goals. The purpose of this study was to determine the effect of self-efficacy on the learning outcomes of public elementary school students in Kupang. This research is a quantitative research with t test data analysis. The sample in this study amounted to 360 students spread across 40 public elementary schools in the city of Kupang. The regression equation in this study is βYX with a tcount of 3.86> ttable of 1.967 and a significant value of 0.00. There are three indicators that observe self-efficacy, namely talent, effort, context. The indicator that contributes to improving student learning outcomes is 44% effort. Based on these results it can be concluded that selfefficacy contributes to improving student learning outcomes in SDNs throughout Kupang; where effort (effort) is an aspect that dominates the achievement of student learning outcomes.